2019
DOI: 10.1016/j.jhsg.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Triangular Fibrocartilage Complex Lesions: A Review of Outcomes

Abstract: Triangular fibrocartilage complex (TFCC) lesions of the wrist are primarily managed nonsurgically. Patients with persistent pain and/or instability may elect to undergo surgery (debridement, open repair, or arthroscopic repair). The current literature is unclear as to the preferred surgical technique. The purpose of this study was to review the literature and determine whether any surgical procedure was superior to others in the surgical management of TFCC lesions. Methods: We performed a thorough literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Recent reviews on surgical management of TFCC injuries observed that both open and arthroscopic repair techniques achieved improvement in patient-reported and functional outcomes, and there was no evidence of one technique being superior to another. 3,16,17 Nakamura et al also found that both open and arthroscopic transosseous repair techniques were reliable and successful in treating foveal detachments of the TFCC. 15 Although they reported better overall outcomes in the group that underwent arthroscopic repair compared with open repair, it should be noted that there was a significant discrepancy in their sample sizes-733 patients in arthroscopic repair group and 92 in the open repair group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews on surgical management of TFCC injuries observed that both open and arthroscopic repair techniques achieved improvement in patient-reported and functional outcomes, and there was no evidence of one technique being superior to another. 3,16,17 Nakamura et al also found that both open and arthroscopic transosseous repair techniques were reliable and successful in treating foveal detachments of the TFCC. 15 Although they reported better overall outcomes in the group that underwent arthroscopic repair compared with open repair, it should be noted that there was a significant discrepancy in their sample sizes-733 patients in arthroscopic repair group and 92 in the open repair group.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, despite the various techniques that have been described, there is still no clear consensus as to which technique provides the most optimum results. 3,16,17 Therefore, it was the aim of this study to systematically review the current literature and examine the functional and clinical outcomes as well as complications of surgical repair techniques for traumatic Palmer Type 1B TFCC tears.…”
mentioning
confidence: 99%
“…23 The repair can be open or arthroscopic, and whereas some authors lean on the side of the arthroscopic approach because of less soft tissue unravelling, better visualization, and increased accuracy of diagnosis, there is still no clear consensus on which approach is superior as both produce equally good outcomes. [7][8][9] The mode of repair, in general, is either by creating trans osseous tunnels or using bone anchors, and there are indeed multiple well-described technique papers whose review of overall outcomes shows equally satisfactory results for both methods. 12 Then why do we have to create one more technique for repairing foveal tears using bone anchors when there are already so many techniques out there?…”
Section: Discussion and Expected Outcomesmentioning
confidence: 99%
“…In case of acute presentation or failed conservative management, surgery with the aim of reattaching the TFCC to the foveal insertion site is needed 23 . The repair can be open or arthroscopic, and whereas some authors lean on the side of the arthroscopic approach because of less soft tissue unravelling, better visualization, and increased accuracy of diagnosis, there is still no clear consensus on which approach is superior as both produce equally good outcomes 7-9 . The mode of repair, in general, is either by creating trans osseous tunnels or using bone anchors, and there are indeed multiple well-described technique papers whose review of overall outcomes shows equally satisfactory results for both methods 12 .…”
Section: Discussion and Expected Outcomesmentioning
confidence: 99%
See 1 more Smart Citation